Strategi Implementasi Visi dan Misi dalam Meningkatkan Mutu Pendidikan - Ach Baidowi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of the research is to analyze and describe the process of formulating the vision and mission, determining programs, setting budgets, determining procedures and the impact on quality at the At-Taqwa Integrated Islamic Junior High School, Surabaya. The research was conducted qualitatively using a case study approach. Data collection techniques: documentary interviews and observation. Data processing techniques: reduction, data presentation and conclusion. Data validity techniques with credibility and confirmability. The results of the research show: (1) the process of formulating the vision and mission: the school has 5 visions, namely the vision of solid faith, good morals, optimal achievement, global insight, and caring for the environment, with details of 3 of the Foundation's visions and 2 of the school's development visions (2) strategy implementation: (a) program determination: prepared by the Al-Qur'an, Islamic, Principal, Infrastructure, Student Affairs, English, Public Relations, Curriculum and national examination divisions. (b) budget determination: sourced from central, regional and foundation assistance, (c) procedure determination: carried out within one year according to the schedule prepared by each division. (3) impact: success of the work program, student achievement and teacher achievement. Conclusion: the vision and mission have been implemented very well as evidenced by the existence of relevant work programs from nine divisions which were developed from the school's mission